IMPLEMENTASI MODEL FUZZY MULTIPLE ATRIBUTE DECISION MAKING DENGAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK MENGUKUR KINERJA GURU ( Studi Kasus : SMA Negeri 1 Luragung ) - Dadang Hamdani; Agus Wahyuddin; Ridwan Galih (NUANSA INFORMATIKA, 2011)
Teacher Performance Assessment is a process to evaluate the performance of teacher at a certain period, to raise higher the quality of education through improved teacher quality. As a quality assurance professionalism of teachers in Teaching and Learning Activities (KBM) in SMA Negeri 1 Luragung to assess teacher performance every last semester. Performace assessment useful to drive the spirit of improving the quality of teachers. So it is necessary to facilitate the development of information technology in teacher performance appraisal system. One of these is the development of information technology Decision Support System (DSS). Decision Support System is called as familiar as the Decision Support System which is a set procedure for model-based data processing and assessment to help managers make decisions. Decision-making in this case is the assessment of teacher performance and suggestions - constructive suggestions for teachers in accordance with obtained score. The Decision Support System Process of Teacher Performance Assessment is assessed on four competencies they are pedogagik, personality, social and professional with a variety of additional points. The assessment of teacher performance used Fuzzy MADM Model with Simple Additive Weighting method of settlement, because by using the SAW method can provide decision makers importance weight for each competency to produce a ranking at the end of the assessment process. This research is held at SMAN 1 Luragung. The Decision Support System (DSS) is Â System used to facilitate the school academic for tacher performance assessment.Keywords: Decision Support System, the Teacher Performance Assessment